Effectiveness and Problems of Implementation of Assistance for Witnesses - Novita Irma Yulistyani; Umar Ma'ruf; Aryani Witasari (Universitas Islam Sultan Agung, 2022)
Proof of a crime, the evidence that must be met is at least 2 pieces of evidence. Evidence that must be submitted in proving a crime is evidence in the form of witness statements. Witness testimony will determine whether a crime can be proven or not before the trial. Considering the importance of witness testimony in proving a crime, it should be balanced with legal protection for witnesses, one of which is by providing assistance in the form of medical assistance, psychosocial rehabilitation and/or psychological rehabilitation. This study aims to answer the problems, namely: first, why is assistance needed for witnesses? second, has the implementation of providing assistance for witnesses been effective? Third, what are the problems faced in providing assistance for witnesses and what are the solutions? The research method uses sociological juridical with a legal research approach using secondary data as initial data, which is then followed by primary data in the field or on the community. Primary data was obtained by obtaining directly from the field through unstructured interviews, secondary data obtained through library research consisting of primary legal materials and secondary legal materials. Qualitative data analysis emphasized the analysis on the process of deductive and inductive inference as well as on the dynamics of the relationship between phenomena that observed using scientific logic. The research problems were analyzed using the theory of legal protection, the theory of legal effectiveness and the theory of justice. The results of the research and discussion of this study can be concluded that the reasons for the need for assistance for witnesses are because witnesses are very decisive evidence in the process of proving criminal cases, witnesses must be free and safe in giving testimony and many witnesses need medical assistance, psychological rehabilitation and/or or psychosocial rehabilitation. Regarding the effectiveness of assistance for witnesses, currently it has not been effective. This is due to the legal factors themselves, law enforcement factors and community factors. This is because there are problems from the lack of knowledge by law enforcement officers, the absence of rules that bind law enforcers, the absence of synergy between law enforcement agencies and the lack of socialization to the public regarding the assistance for witnesses.